Affective prosody in grunts of young chimpanzees - Derry Taylor; Guillaume Dezecache; Marina Davila-Ross (Revue de Primatologie)
Humans acoustically encode affective information into their utterances. This ability, known as ‘affective prosody’, takes pre-linguistic roots and plays an important role in human communication throughout the lifespan by enabling listeners to disambiguate the meaning of speakers’ utterances. Adopting a comparative-developmental perspective, we ask whether such an ability may also be present in the vocalisations of young chimpanzees. We examine the acoustic characteristics of grunt vocalisations known to be related to affective expression in other non-human species and show that grunts produced during positive, neutral, and negative contexts can indeed be distinguished on this acoustic basis. Further, our data provide new and unexpected insights into ontogenetic constraints in chimpanzee vocal production, finding that almost all acoustic parameters in early chimpanzee grunts are strongly correlated. We conclude that affective prosody is likely a characteristic of young chimpanzee vocal behaviour and speculate that affect may be more flexibly expressed through call acoustics with increasing age as chimpanzees gain greater control over their vocal apparatus.